Symmetrical and unsymmetrical α,ω-nucleobase amide-conjugated systems - Boncel, Sławomir; Mączka, Maciej; Koziol, Krzysztof K. K.; Motyka, Radosław; Walczak, Krzysztof Z. (Beilstein Journal of Organic Chemistry, 2010)
We present the synthesis and selected physicochemical properties of several novel symmetrical and unsymmetrical α,ω-nucleobase mono- and bis-amide conjugated systems containing aliphatic, aromatic or saccharidic linkages. The final stage of the synthesis involves condensation of a subunit bearing carboxylic group with an amine subunit. 4-(4,6-Dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMT-MM) was found to be a particularly effective condensing agent. The subunits containing carboxylic groups were obtained by acidic hydrolysis of N-1 Michael adducts of uracils or N-9 Michael adducts of 6-chloropurine with methyl acrylate. The amines used were aliphatic/aromatic diamines, adenine, 5-substituted 1-(ω-aminoalkyl)uracils and 5′-amino-2′,5′-dideoxythymidine. The title compounds may find application as antiprotozoal agents. Moreover, preliminary microscopy TEM studies of supramolecular behaviour showed that target molecules with bolaamphiphilic structures were capable of forming highly ordered assemblies, mainly nanofibres.
Keywords: amides; antiprotozoal agents; coupling; nucleosides; self-assembly